(untitled) (Medicine Today, 2023)
Introduction with objective: Preeclampsia is a major cause of maternal and fetal morbidity and mortality in Bangladesh. This study aimed to estimate C-reactive protein (CRP) level among patients with preeclampsia and to compare with those of trimester-matched normal pregnancy. Materials and Methods: : This cross-sectional study was done from January 2005 to December 2006 at the different tertiary care hospital at Dhaka. A total of 33 preeclamptic and 33 normal pregnant women in the third trimester were enrolled in the study. The PE patients were divided into two groups: mild hypertension [diastolic blood pressure (DBP) <110 mm Hg] and severe hypertension (DBP _110 mm Hg). Similarly the patients were divided into two groups on the basis of proteinuria, group I ( 2+>=1gm/l) and group II (3+_3gm/l). Both PE and control groups were matched for their age and parity. Estimation of serum CRP was done by Turbulometry method. Results: CRP concentration (mg/l) was 4.55±2.83 in control group and 23.52±24.85 in PE group which was significantly higher than in control group. CRP level was significantly higher (p<0.001) in severe PE than in mild PE group. Significant difference was also seen between the groups subdivided on the basis of proteinuria (p<0.05). In the whole population CRP values showed significant positive correlation with systolic and diastolic blood pressure (p<0.001) and significant negative correlation with gestational age at delivery and birth weight (gestational age: p<0.05, birth weight: p<0.001). Conclusion: Maternal CRP concentration was higher in patients with preeclampsia and was correlated with disease severity. Medicine Today 2023 Vol.35(1): 1-6